Analisis Perubahan Iklim dengan Kejadian Demam Berdarah Dengue di Kota Banda Aceh Tahun 2022-2024 - Sahayati Windy Afreli; Fahmi Ichwansyah; Putri Ariscasari (Pelantar Press, 2025)
Dengue Hemorrhagic Fever is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. Climate change has had a significant impact on the increase in cases of Dengue Hemorrhagic Fever, where there is a tendency for an increase in DHF cases during the transition season. This study aims to analyze the relationship between climate change (climate factors) and DHF incidence in Banda Aceh City in 2022-2024. This study uses a descriptive study design with secondary data related to climate change and the incidence of Dengue Fever in Banda Aceh City in 2022-2024. This study uses multiple linear regression tests. The sample in this study is all monthly observations of DHF incidence, Temperature, Humidity, Wind Speed, and Rainfall in the period 2022-2024. The results of the study explain that there is no influence between temperature and the incidence of dengue fever in Banda Aceh City in 2022-2024 with a p value = 0.936 0.05, there is no influence between humidity and the incidence of dengue fever in Banda Aceh City in 2022-2024, there is no significant influence between wind speed and the incidence of dengue fever in 2022-2024 with a p value = 0.096 0.05, There is a relationship between rainfall and the incidence of dengue fever in Banda Aceh City in 2022-2024 with a p value = 0.022 0.05. It is recommended for the public to always be alert to dengue fever, especially if rainfall increases. The relevant agencies can develop a weather-based early warning system to notify the public about the increased risk of dengue fever during high rainfall